2009
DOI: 10.1200/jco.2009.27.15_suppl.e22226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of Chinese patients with BRCA related breast cancer

Abstract: e22226 Background: Breast cancers due to underlying germline BRCA1 and BRCA2 mutations are associated with particular pathological features that may differ from sporadic breast cancers. We report clinical and pathologic characteristics of breast cancer in a clinical cohort of high risk Chinese women with BRCA mutations and those without mutations. Methods: 202 high risk women based on their age and family history were recruited from March 2007 to November 2008. Medical information was prospectively collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…Interestingly, the BRCA1/2 ‐positive rate was similar among different age groups in the OV cohort, which was different from the BROV cohort, as well as the BRCA ‐positive breast cancer patients in our previous study (Kwong et al, 2009). The majority of these two groups of cancer patients were diagnosed at the age between 20 and 44 or later (Table S3a).…”
Section: Resultscontrasting
confidence: 93%
“…Interestingly, the BRCA1/2 ‐positive rate was similar among different age groups in the OV cohort, which was different from the BROV cohort, as well as the BRCA ‐positive breast cancer patients in our previous study (Kwong et al, 2009). The majority of these two groups of cancer patients were diagnosed at the age between 20 and 44 or later (Table S3a).…”
Section: Resultscontrasting
confidence: 93%
“…Clinical and genetic characteristics of breast cancer patients with pathogenic gBRCA1/2 mutations were investigated in the present study. In consistence with previous reports, about half of our patients were diagnosed before age 40, and majority were premenopausal [4,39]. These patients also presented with other high risk features, such as family history of breast cancer, co-occurrence of contralateral breast or ovarian cancer, and high Ki-67 index [5,7,40].…”
Section: Discussionsupporting
confidence: 88%
“…In multivariable regression analyses, we found that the risk factors significantly associated with BRCA PV carrier status in this study were consistent with previously published findings from Asian countries, including younger age of diagnosis, bilateral breast cancer, ER-negative status, HER2negative status, higher grade, and presence of first-degree family history of breast cancer or ovarian cancer. 20,22,[30][31][32][33][34][35][36][37][38] We found that all the BRCA carrier prediction models and the MCC were more sensitive (sensitivity/detection rate) and accurate (discrimination) for BRCA1 than BRCA2, which is likely to be driven by the stronger association between BRCA1 and the ER-negative status, TNBC subtype, and ovarian cancer family history. [39][40][41][42][43] Indeed, several studies have previously demonstrated that the use of pathologic characteristics, namely ER and TNBC, improved the sensitivity and discrimination for BRCA1 when selecting individuals for germline genetic testing in high-risk breast cancer patients.…”
Section: Discussionmentioning
confidence: 79%
“…In multivariable regression analyses, we found that the risk factors significantly associated with BRCA PV carrier status in this study were consistent with previously published findings from Asian countries, including younger age of diagnosis, bilateral breast cancer, ER-negative status, HER2-negative status, higher grade, and presence of first-degree family history of breast cancer or ovarian cancer. 20,22,30-38…”
Section: Discussionmentioning
confidence: 99%